Coplanar microwave integrated circuits - Wolff, Ingo (Wiley-Interscience, 2006)
Coplanar Microwave Integrated Circuits sets forth the theoretical underpinnings of coplanar waveguides and thoroughly examines the various coplanar components such as discontinuities, lumped elements, resonators, couplers, and filters, which are essential for microwave integrated circuit design. Based on the results of his own research findings, the author effectively demonstrates the many advantages of coplanar waveguide technology for modern circuit design.